PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR PEMBELAJARAN IPS PADA SISWA KELAS IV SD TAMBAKPLOSO TURI LAMONGAN - Kiky Chandra Silvia Anggraini (Universitas Islam Lamongan, 2018)
One of the problems at school and society is the low results of social studies learning. During this time social science is identical with boring learning so students are not interested in learning. The use of lectures used by the majority of teachers will be replaced by the application of the guided inquiry learning model. This type of research is a pre-experiment that involved class IV at SDN Tambakploso. Use of written tests as instruments for data collection. Sampling in this study was carried out with saturation. The research data were analyzed through SPSS version 25.00. Based on the results of the pretest and posttest in the experimental class that uses guided inquiry is more effective than the control class that performs pure inquiry to increase students' social sensitivity. Analysis with the t test found a significance value of 0,000 or smaller than 0.05 which indicates an alternative hypothesis was accepted